A crise financeira de 2008: os discursos e as estratégias do governo e dos fundos de pensão - Jardim, Maria Chaves [UNESP] (Universidade do Estado do Rio de Janeiro (UERJ), Instituto de Estudos Sociais e Políticos (IESP), 2013)
This article focuses on the financial crisis beginning in 2008. Drawing on the work of Lebaron (2010; 2011) and (Grün 2010), the study seeks to grasp the cognitive dimension of the crisis through the discourses produced (and reproduced) by members of the Brazilian government involved in controlling the crisis and by the pension fund sector and its strategies. The method was based on analysis of documents produced by the pension fund sector and the Lula Administration in 2008 and the spinoffs of the discourses and strategies. The text indicates the construction of a discourse emphasizing the importance of state regulation (as opposed to market self-regulation) and the central role of pension funds during the process, since they partially abandoned government bonds and migrated to productive investment, in alliance with the private equity sector, especially in financing construction works under the Growth Acceleration Program.

Dans cet article, on examine la crise commencée en 2008. Sous l'inspiration des travaux de Lebaron (2010; 2011) et Grun (2010), on essaie de saisir la dimension cognitive de la crise, à travers les discours produits (et reproduits) par des membres du gouvernement engagés dans le contrôle de la crise et du secteur des fonds de pension, ainsi que de leurs stratégies effectives. La méthode couvre l'analyse de documents produits par le secteur des fonds de pension et par le gouvernement Lula pendant l'année 2008, ainsi que les retombées des discours et des stratégies menées. Le texte montre la construction d'un discours soulignant l'importance de la régulation par l'État (par opposition au discours de l'autorégulation du marché) et la participation centrale des fonds de pension pendant le processus, puisque ceux-ci avaient abandonné en partie les titres publics et migré vers l'investissement productif, alliés au secteur de private equity, surtout en ce qui concerne le financement des chantiers du Programme d'Accélération de la Croissance.
The 2008 financial crisis: government discourses and strategies and pension funds in Brazil
La crise financière de 2008: les discours et les stratégies du gouvernement et des fonds de pension
Keywords: cognitive dimension; financial crisis; discourse production; strategies; pension funds; government